2003
DOI: 10.1167/iovs.03-0122
|View full text |Cite
|
Sign up to set email alerts
|

Lenticular Oxygen Toxicity

Abstract: High oxygen load has a toxic effect on bovine lenses in organ culture. These effects appear to be cumulative: the higher the oxygen partial pressure and the greater the number of exposures, the more severe the changes observed in the lenses. Changes marking toxicity follow the route of oxygen diffusion into the lens, from the periphery to the center. Cautious interpretation of the results may indicate a role of oxygen (and/or its derivatives) in human cataract formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
1
19
0
1
Order By: Relevance
“…Several studies have shown that exposure of the lens to increased oxygen is associated with increased opacification of the lens nucleus or frank nuclear cataracts. 33,36,37,[53][54][55] Epidemiologic studies revealed that lens thickness is a significant risk factor in age-related cataract formation. 39,40 In these studies, individuals with smaller lenses at the time of examination were more likely to have cortical cataracts, whereas those with larger lenses more frequently had nuclear cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that exposure of the lens to increased oxygen is associated with increased opacification of the lens nucleus or frank nuclear cataracts. 33,36,37,[53][54][55] Epidemiologic studies revealed that lens thickness is a significant risk factor in age-related cataract formation. 39,40 In these studies, individuals with smaller lenses at the time of examination were more likely to have cortical cataracts, whereas those with larger lenses more frequently had nuclear cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…As is the case in other tissues, the high content of glutathione in the lens is believed to protect the thiols in structural proteins and enzymes and thus allow for proper biological function. [8][9][10][11] Aging lenses or lenses under oxidative stress exhibit an extensively consumed GSH pool. The lens depends on a balanced redox state to maintain transparency.…”
Section: Importance Of Redox Regulation In Lensmentioning
confidence: 99%
“…Exogenous sources include ultraviolet light, ionizing radiation, chemotherapeutics, and environmental toxins. [8][9][10][11][12] Of the exogenous sources, polycyclic aromatic hydrocarbons are an important risk factor for the cataract formation through lipid peroxidation generated from the redox-imbalance in the cell, namely, oxidative stress. Additionally, ROS also directly damage the antioxidant-system, indicating that such damage leads to a lens weakened in certain aspects of the innate protection against oxidative stress.…”
Section: Importance Of Redox Regulation In Lensmentioning
confidence: 99%
See 1 more Smart Citation
“…Протеини сочива који чине највећи део његове солидне масе имају дуг животни век и током старења долази до њиховог оштећења под дејством светлости, тачније ултраљубичастих зрака (79,192).…”
Section: биохемијске промене у сочиву током развоја катарактеunclassified